GE_GERICHTE P/766/2010 vom 8. Juli 2014 - GE Cour de justice (2014)
INFRACTIONS CONTRE L'ADMINISTRATION DE LA JUSTICE; BLANCHIMENT D'ARGENT; CONFISCATION(DROIT PÉNAL) | CP.305bis; LBA.3; LBA.6; CP.71.1; CP.71.3